Genetic Diversity of Invasive Spartina alterniflora Loisel. (Poaceae) Introduced Unintentionally Into Japan and Its Invasion Pathway - Maebara, Yu; Tamaoki, Masanori; Iguchi, Yuka; Nakahama, Naoyuki; Hanai, Takaaki; Nishino, Atsushi; Hayasaka, Daisuke (Frontiers in Plant Science, 2020)
Among invasive species, aquatic plants pose serious threats to local biodiversity and ecosystem functions. Spartina alterniflora Loisel. (Poaceae), native to the eastern United States, was introduced unintentionally into Japan (Aichi and Kumamoto Prefectures) at around 2010. This invasive species could easily and rapidly spread to estuarine areas of Japan via vigorous trade and transport, making the prediction of its future invasion necessary. Here, the distribution and structure of the genetic variation of S. alterniflora in Japan were examined using chloroplast DNA (cpDNA) and microsatellite genotyping analyses for clarifying its invasion route and process. According to the cpDNA analysis, S. alterniflora populations in Japan had a single haplotype (haplotype C4) that is the most dominant genotype around the Florida Peninsula, the region of its origin, and is also widely found in the introduced populations in the East Asia. Microsatellite analysis also showed a loss of genetic diversity in Japanese S. alterniflora populations (allelic richness (AR)=1.20-1.39) compared with that in its native region (AR=4.58-4.59), suggesting a founder effect on S. alterniflora that might have occurred after invasion of the species into Japan. The principal coordinate analysis and The STRUCTURE analysis indicated that no gene mixing among Japanese local populations (Aichi, northern and southern Kumamoto) was observed, indicating that Spartina invasion occurred independently into these regions. Among the three regions, trading between the ports of northern Kumamoto and the U.S. was obviously lower than trading with China. We concluded that invasive S. alterniflora might have independently invaded Japan at different times through an East Asia route, particularly via China (i.e., secondary introduction). Therefore, it is important to strengthen the quarantine control on the importation of commodities, especially of transport vehicles at potential donor spots (i.e., border control/border biosecurity system), and to share information networks on invasive species between each region/port for minimizing further risks of biological species such as Spartina.